Pets and Human Health in Germany and Australia: National Longitudinal Results - Bruce Headey; Markus M. Grabka (Social Indicators Research, 2007)
The German and Australian longitudinal surveys analysed here are the first national representative surveys to show that (1) people who continuously own a pet are the healthiest group and (2) people who cease to have a pet or never had one are less healthy. Most previous studies which have claimed that pets confer health benefits were cross-sectional. So they were open to the objection that owners may have been healthier in the first place, rather than becoming healthier due to owning a pet. In both countries the data show that pet owners make about 15% fewer annual doctor visits than non-owners. The relationship remains statistically significant after controlling for gender, age, marital status, income and other variables associated with health. The German data come from the German Socio-Economic Panel in which respondents have been interviewed every year since 1984 (N = 9723). Australian data come from the Australian National Social Science Survey 2001 (N = 1246).
Additional information: The final publication is available at www.springerlink.com: http://dx.doi.org/10.1007/s11205-005-5072-z
Keywords: 330; doctor visits; health; panel surveys; pet owners; Gesundheit; Gesundheitskosten; Panel; Deutschland; Australien